Degradation of acid red 8 dye using photo-fenton reaction mediated by titanium modified catalysts - Bento, André C. [UNESP]; Emídio, Elissandro S. [UNESP]; Hammer, Peter [UNESP]; Nogueira, Raquel F. P. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2019)
Catalysts prepared by co-precipitation of iron and titanium were evaluated in heterogeneous photo-Fenton degradation of the azo dye Acid Red 8 under blacklight irradiation. Materials with different titanium contents (0 < Ti/Fe < 0.6) were characterized using X-ray diffractometry, scanning electron microscopy, X-ray fluorescence spectroscopy, specific surface area and X-ray photoelectron spectroscopy. Hematite was identified as main phase in materials with lowest Ti content, while titanomaghemite was predominant at high Ti content. Highest degradation was obtained using titanium free catalyst due to iron leaching, which promoted a homogeneous reaction. Addition of Ti led to a heterogeneous process with a maximum when Ti/Fe = 0.40 achieving 0.76 mol of dye mineralized per mol of soluble iron after 90 min, using 10 mmol L-1 H2O2 at pH 5.6, value at least three times higher than that observed for catalysts with lower Ti content. The results indicate that Ti stabilizes the catalyst and increases its heterogeneous activity in photo-Fenton process.
Keywords: Azo dye; Hematite; Iron leaching; Titanium; Titanomaghemite